Healthcare workers' clinical knowledge on maternal and newborn care in Ethiopia: findings from 2016 national EmONC assessment - Theodros Getachew Zemedu; Aster Teshome; Yared Tadesse; Abebe Bekele; Emily Keyes; Patricia Bailey; Ana Lorena Ruano (BMC, 2019)
Abstract Background Improving maternal and newborn health indicators are key if Ethiopia is to achieve the Sustainable Development Goals. To do so, women need access to skilled attendance at birth and emergency obstetric and newborn care. To maximize their impact, understanding gaps in workers' knowledge is required to remedy the weakness. This assessment determines knowledge levels of clinical management of maternal and newborn healthcare and factors that influence knowledge. Methods This study used data from the National Emergency Obstetric and Neonatal Care assessment conducted in 2016. Provider knowledge for MNH was assessed by interviewing providers. Respondents were scored on each question by calculating the number of correct responses provided out of the total possible answers, and standardizing this to a scale of 100. Mixed linear regression was used to determine individual and contextual factors associated with the score. Results A total of 3800 interviews with complete data were included in this study. Most respondents were diploma midwives (73%), BSc midwives (11%) and diploma nurses (10%). On average, midwives scored 60 out of 100 on the question regarding the primary aspects of focused antenatal care and elements of a birth plan. Half of the midwives and health officers, and one-third of nurses knew to provide a loading dose of magnesium sulphate. Midwives scored 90% on the steps of active management of third stage of labor. In the mixed linear regression, working in a private for profit facility, health center/clinic, rural area, or in a facility with a protocol on referral/counter referral predicted lower knowledge scores. More positive scores were associated with work environments that had a computer, internet, and protocols on safe abortion care, management of selected obstetric topics, integrated management of pregnancy, childbirth, postnatal, and newborn, care for low birth weight including kangaroo mother care, and treatment of infection in young infants. Conclusion With regard to most knowledge related questions, health officers and midwives scored similarly. Providers scored substantially better on routine intrapartum and newborn care than on aspects related to care for complications. A substantial proportion of providers indicated that they would never give a loading dose of magnesium sulphate.